(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To build and validate a clinical protocol aimed at evaluating the dermatological sensitivity caused by collection devices and adjuvants used by people with stomas. Methodology: Methodological research, developed between 2020 and 2021, for the construction and validation of a dermatological evaluation protocol for people with elimination stomas. The construction of the protocol went through the steps: theoretical situational diagnosis, survey of the theoretical framework and development of the protocol. Results: For validation, 21 judges, nurses, with experience in the area of enterostomal therapy, were recruited, whose instrument for content validation evaluated objectives, structure and relevance of the technology, being made available via e-mail through an electronic form on the Google Forms platform. For data analysis, descriptive statistics and the calculation of content validation index were used. A global score of agreement between the judges of 0.92 was obtained. Conclusion: It is concluded that the protocol created has a practical basis and validation, application versatility, enabling a care process that is more congruent with the reality of the person with an elimination stoma.